Marketing analysis of the global market of telematics transport and information management systems - I. Yu. Okolnishnikova; A. V. Keller; V. Ya. Konks (Вестник университета)
The article presents the results of marketing analysis of the global high-tech market of telematics transport and information management systems. The main trends in and factors of development of automotive telematics devices’ product line are analyzed. Dynamics of growth of the most important segments of the market under study are identified and described. The existing specifics of the development of key geographical consumer microsegments, that is, the markets of North America, Europe and the Asia-Pacific region, are provided, and corresponding forecast indicators are presented. The main product macrosegments, namely navigation and satellite systems, unmanned vehicles, ADAS systems and insurance telematics, are studied in the same manner. Based on the data obtained, the authors describe the existing levels of vehicle autonomy, which significantly affect the indicators of market growth. An overview of the key high technologies ensuring the stability of the transport telematics market is provided, and the average time needed to reach the plateau of their productivity is measured.